Fertility Decline in Malawi: A Decomposition Analysis - Palamuleni, Martin Enock (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2024)
Fertility in Malawi has been declining since the late 1980s. Total Fertility Rate is reported to have declined by 1.1 children per woman from 5.7 in 2010 to 4.6 in 2015. This reduction indicates a continuing rapid decline in fertility in the country. In view of the foregoing, this study aims to examine the influence of the age structure of the population, nuptiality, and marital fertility on fertility in Malawi. This study used the Malawi Demographic and Health Survey data from 1992, 2000, 2004, 2010, and 2015–2016. Standardization and decomposition methods were used to re-examine fertility trends in Malawi. The results confirms that fertility is declining in Malawi and the fall is clustered among women younger than 30 years of age. The contribution of marital fertility to the decline of Total Fertility Rate was 65.0% during the period 1992–2000, 89.5% during 2000–2004, 2.6% during 2004–2010, and 4.3% during 2010–2015, respectively. Over the same period, the respective contribution of the proportion married was 29.4%, 10.8%, 77.9%, and 92.6%. These percentages suggest that marital fertility followed by proportion of married were important factors before 2005. After 2005, fertility levels and patterns in Malawi are largely influenced by nuptiality. However, there is need for further studies to explain the marriage and fertility nexus in the Malawian context.